Основні реформи конституційного устрою Італії - Чернеженко, О.; Chernezhenko, O. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті висвітлено основні реформи політичної системи та конституційного устрою Італії, їх риси та основні положення. Досліджено територіальний устрій Італії; механізми для упорядкування міжрівневих урядових стосунків; питання муніципальних та регіональних конференцій. Проаналізовано проблеми регіоналізації. Приділено увагу питанню балансу повноважень, компетенції та відповідальності між центральними органами влади та органами місцевого самоврядування. The article highlights the major reforms of the political system and constitutional order in Italy, their features and guidelines. In the focus of the study are the issues of the territorial structure of Italy, its regionalization; mechanisms for regulation of the interlevel government relations; issues of municipal and regional conferences. The emphasis is laid on the issues concerning balancing powers, competence and responsibilities of the central government and local self-governing bodies. The key findings of the study show, that the idea of the reform in 2001 has not been utilized completely, since it resulted only in the distribution of power in favor of the regional level. In the early 1990s, the central state power was de-legitimized through a decade of weak governance. As a result of the reform of 2001, an intricate constitutional structure was established, having caused disproportions throughout the country. The new constitutional reform is aimed at establishing a new balance between political players in Italy, which means, first of all, a new approach to distribution of powers in favour of the state. Without this reform in the short or medium perspective, this territory may become unsufficiently competitive both in terms of domestic productivity and in terms of attracting foreign investment. Much confusion at the local level prevents serious investments into any kind of economic activity.
Major Reforms of the Constitutional Order in Italy
Keywords: Італія; компетенція; реформи; регіони; децентралізація; референдум; політичні сили; органи самоврядування; Italy; competence; reforms; regions; decentralization; referendum; political forces; bodies of self-government